Vertical FDI versus Outsourcing : The Role of Host Country Human Capital - Goswami, Arti Grover (Taylor and Francis, 2013)
The existing literature on offshoring neglects the importance of host country conditions in affecting the boundaries of a firm. In this paper, we focus on the role of the host country's human capital in affecting the organization of offshore production. Acknowledging that an input is produced offshore only after training the host labor, we propose that this training cost depends on the human capital gap between the home and the host country. Our model finds that a sourcing firm prefers to offshore production internationally only if the human capital gap between the home and the host country is below a threshold. Secondly, as the human capital gap increases, the probability for international outsourcing vis-à-vis intra-firm trade increases. Finally, as opposed to conventional wisdom, our model shows the possibility of outsourcing inputs of a high-tech good when the human capital gap between the home and the host is high.